Pemasaran Online Dengan Memanfaatkan Market Place dan Strategi Meningkatkan Penjualan di Masa Pandemi Covid 19 di SMK IPIEMS Surabaya - Nugroho, Novianto Eko; Cahyono, Krido Eko; Suryawirawan, Okto Aditya (Jurnal Abadimas Adi Buana, 2021)
The impact of the corona virus pandemic (covid-19) is felt in all aspects of community life, especially Micro, Small and Medium Enterprises (MSMEs). Through various training and mentoring activities which include the use of online marketing and sales improvement strategies is a concrete and concrete manifestation in an effort to increase entrepreneurial awareness among students of SMK IPIEMS Surabaya. The purpose of the realization of Community Service Activities through Online Marketing Training and Assistance by Utilizing the Shopee Mobile Marketplace Platform and Strategies to Increase Sales in the Covid Pandemic Period at SMK IPIEMS Surabaya is to provide insight and understanding of the importance of the ability to do online marketing and increase sales of goods to consumers. students of SMK IPIEMS Surabaya so that when they graduate they become entrepreneurs. In addition to lecturers from the School of Economics Indonesia Surabaya as the implementer of this Community Service activity, the counseling and mentoring carried out also involves strategic partners, namely Shopee Indonesia. The results obtained from this training and mentoring activity are students' understanding of the online marketing of the Mobile Marketplace Platform and sales improvement strategies, in order to increase product value and the resulting sales turnover.